1997
DOI: 10.1007/bf01372149
|View full text |Cite
|
Sign up to set email alerts
|

Gastroschisis: can the morbidity be avoided?

Abstract: Although the mortality associated with gastroschisis (GS) has fallen markedly over recent years, postoperative morbidity and the incidence of complications remain high. Many different factors may contribute to this morbidity; the aim of this study was to determine which factors contributed most. Measures of morbidity used were time to full oral feeding (FOF), time on parenteral nutrition (PN), age at discharge, and incidence of complications. Between 1969 and 1995, 44 neonates with GS were treated; there were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
13

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 22 publications
2
17
0
13
Order By: Relevance
“…Taking into account both mortality and morbidity data, the authors of the different studies gave a recommendation on whether to perform an elective CS in cases with prenatally diagnosed gastroschisis. In all, three papers recommended CS 15,23,31 nine papers did not recommend CS 13,16,19,20,24,25,27,29,33 six papers said that it does not matter what you do 21,22,28,30,32,34 and four papers did not give any recommendations 14,17,18,26 . The comparable data on delivery in cases of omphalocele were equally inconclusive.…”
Section: Mode and Timing Of The Deliverymentioning
confidence: 95%
“…Taking into account both mortality and morbidity data, the authors of the different studies gave a recommendation on whether to perform an elective CS in cases with prenatally diagnosed gastroschisis. In all, three papers recommended CS 15,23,31 nine papers did not recommend CS 13,16,19,20,24,25,27,29,33 six papers said that it does not matter what you do 21,22,28,30,32,34 and four papers did not give any recommendations 14,17,18,26 . The comparable data on delivery in cases of omphalocele were equally inconclusive.…”
Section: Mode and Timing Of The Deliverymentioning
confidence: 95%
“…The silo is then gradually reduced until reduction is achieved and final abdominal closure is carried out in theatre. Some studies have suggested that silo repair cases have an increased complication rate and longer length of hospital stay than those undergoing primary closure (Luck and Scrutton, 1997); (Nicholls et al 1993); (Blakelock et al 1997) however Tawil et al (1995) found similar outcomes in both groups. More recently some units have used a minimal intervention method of manual reduction of the defect without anaesthesia or sedation in an incubator on the paediatric surgical unit (Bianchi and Dickson, 1998); (Kimble et al 2001), (Jona, 2003), with apparently similar outcomes to primary closure in theatre.…”
Section: Post-natal Management and Outcomementioning
confidence: 98%
“…Many observational studies have looked at the effect of mode of delivery upon the outcome of gastroschisis cases (Sakala et al 1993); (Adra et al 1996); (Bethel et al 1989); (Blakelock et al 1997); (Novotny et al 1993); (Quirk et al 1996); (How et al 2000); (Lewis et al 1990); (Rinehart et al 1999); (Snyder, 1999); (Moretti et al 1990); (Tawil and Gillam, 1995). Although some have suggested that elective caesarean section at or before the onset of labour may benefit a gastroschisis fetus when compared with undergoing labour and vaginal delivery (Sakala et al 1993) the majority of studies have found that delivery by caesarean section confers no benefit in terms of mortality and morbidity (Adra et al 1996); (Bethel et al 1989); (Blakelock et al 1997); (Novotny et al 1993); (Quirk et al 1996); (How et al 2000); (Lewis et al 1990); (Rinehart et al 1999); (Snyder, 1999); (Moretti et al 1990); (Tawil and Gillam, 1995). However, due to the rarity of gastroschisis, most of these studies were small, retrospective and observational.…”
Section: Delivery and Perinatal Managementmentioning
confidence: 99%
“…Infants with gastroschisis have multiple risk factors for poor long-term outcome, including prematurity in two thirds, 2 and poor in utero growth in 20%. 3 Despite absence of extreme prematurity in most cases, all infants with gastroschisis are at risk for the development of necrotizing enterocolitis with subsequent bowel injury or loss. In addition, 11% of infants have complex gastrointestinal involvement (atresia, stenosis, perforation, necrosis or volvulus) which requires surgical resection of bowel.…”
Section: Introductionmentioning
confidence: 99%